(untitled) (Comparative & International Education Series, 2022)
I was thrilled when I received a call from Human Resources in July 2016 about my successful contract employment as an Associate Lecturer (Level A) at a university in Melbourne, Australia. I did my PhD in Australia, and I was fortunate that, within 7 months of my post-PhD graduation, I was employed there. During my PhD I got married, and we decided to stay in Australia and not return home to our home country, Malaysia, at least for several years. Therefore, receiving the job offer mattered, because I will have a job which is equivalent to my qualifications. As an international PhD graduate, the job offer also endorsed my knowledge, skills and boosted my self-confidence.